Lymfactin® gene therapy with vascularized lymph node transfer reduces compression-free swelling and enhances quality of life in breast cancer-related lymphedema: Final Phase I trial results - Pajula, Susanna; Saarikko, Anne; Suominen, Sinikka; Kaartinen, Ilkka; Kiiski, Juha; Suominen, Erkki; Viitanen, Tiina; Mäki, Maija; Seppänen, Marko; Lahdenperä, Outi; Alitalo, Kari; Hartiala, Pauliina (Elsevier, 2026)
Background
Lymfactin® is a gene-therapy vector encoding vascular endothelial growth factor C designed to promote lymphatic vessel growth. It is administered during vascularized lymph node transfer (VLNT) to treat breast cancer-related lymphedema. This study presents the final efficacy and long-term safety results of the Lymfactin® Phase I trial.
Methods
Between 2016 and 2018, 12 patients with breast cancer-related lymphedema received a therapeutic dose of Lymfactin® injected into the VLNT flap with or without autologous breast reconstruction. Patients were followed up annually for 4 years.
Results
The mean seven-day swelling volume, defined as the volume change after one week of compression interruption, decreased clearly compared to baseline at the three-year follow-up: 105.7 ±161.0 ml vs. 14.9 ± 174.2 ml. The total lymphedema quality of life (LQOLI) scores improved significantly from baseline to the three-year follow-up (p = 0.02). Within the LQOLI subdomains, physical (p < 0.01) and psychosocial (p = 0.01) scores showed significant improvement over 3 years postoperatively. Six of the 12 participants reduced or discontinued compression garment use within 3 years postoperatively. This group exhibited significantly smaller upper extremity volume differences than those who continued regular compression use (317.8 vs. 923.2 ml, p = 0.04). No serious adverse events were reported, and all the patients remained alive during the four-year follow-up.
Conclusion
This prospective multicenter study demonstrated that Lymfactin® with VLNT is safe and well tolerated. Although volume reduction was most evident in the first year, half of the patients reduced or discontinued compression use, and quality of life improved over long-term follow up.